Strengthening Brand Knowledge through Brand Orientation and Brand Involvement - Rafidah Salma Mardhiyah; Nurul Azizah (Nusantara Science and Technology Proceedings)
In the era of global competition, an organization is required to develop its existence. One effort to develop the existence of the organization is to strengthen the brand so that the loyalty and satisfaction of customers or users increases. Of course, this brand will become a distinctive feature in the organization. Brand knowledge is the first step in strengthening the organization's brand, especially for internal actors. As the theoretical foundation in the current research is internal branding, which consists of three variables, namely: Brand Orientation, brand involvement, and brand knowledge. The study sampled in this study was 285 employees at UPN "Veteran" East Java. each variable is measured using indicator items adopted from previous studies using a Likert scale. The research method uses quantitative with a questionnaire as an instrument and hypothesis testing is done with Smart PLS software. Hypothesis test results indicate that there is a significant influence between brand involvement and brand knowledge, brand orientation with brand involvement, and insignificant influence between brand orientation and brand knowledge.